Sensors for workplace safety - Ong, Zhi Huay (2018)
This report describes a custom-built-tracking and motion detection device using the technology of Inertia Measurement Unit (IMU) and Global Positioning System (GPS) which will be connected wirelessly via third generation (3G) network to a smart phone. The functionality of the device is to locate and monitor movements of the workers at construction sites. This will greatly improve the safety and communication system at construction sites. Safety is the most important factor in engineering industry especially in construction sectors. The construction process is considered risky endeavour due to the high frequency of work-related injuries and fatalities. As much as workers are cautions in their actions, unforeseen accidents might still happen. Therefore, it is of utmost importance to have a collection of safety data to improve strategy development. By implementing a wearable technology that has the potential to obtain result-oriented data and providing real-time information of workers location, it will allow immediate action to be taken to impede the accident from getting worse. The purpose of this device is to track worker’s location at construction sites as a form of monitoring system by using technology from GPS and 3G network. In most engineering industries, workplace safety is often the key emphasis in the company especially in the construction industry. This device will be able to improve the safety and communication system at construction sites by sending real-time location to supervisors. Such monitoring system is very useful as supervisors will be able to locate worker’s location at any point especially when accidents occur.